EGEE roll: a framework to fully-automated site deployment & management - Pina, António Manuel Silva (2008)
The work focuses on an easy to use framework that automates the deployment and management of all EGEE components in sites where a common Grid operating environment must be rapidly setup. The approach is based on the Rocks Toolkit and is supported around the concept of ROLL, an isolated package containing software and configuration files, used to install and configure specific software packages and to create new appliances with little involvement from system administrator.